Dynamic and static friction measurements of elastomer footwear blocks on ice surface. (February 2023) - Jakobsen, Lasse; Auganaes, Sondre Bergtun; Buene, Audun Formo; Sivebaek, Ion Marius; Klein-Paste, Alex
Abstract: This study conducted friction experiments of three elastomer block materials on ice (low pressure injection of polyurethane (PU), injection moulding of a thermoplastic polyurethane (TPU) and vulcanization of rubber (RU)), with a linear tribometer operating under four different ambient air temperatures (−10 to 0 °C) and six different sliding velocities (0.3–5 m/s). At low temperatures (−10 °C and −5 °C), the RU material showed the highest dynamic and static friction. However, at high temperatures (−2 °C and 0 °C) the PU revealed the highest dynamic friction and highest static friction at 0 °C. We discuss the physical phenomena's of elastomer friction on ice and in relation to the application of footwear slipping on ice. Highlights: Slipping accidents simulated by biofidelic friction testing of elastomers on ice. PU outsole material on warm ice provides higher static friction coefficient compared to TPU and RU materials. RU outsole material revealed higher dynamic friction coefficient on cold (−10 to 5 °C) ice compared to TPU and PU materials. Hybrid outsole constructions combining materials, composites and design solutions may be able to accommodate slip resistance.